Marketing system of wild and hatchery reared fry of Penaeus monodon and its value chain in Bangladesh - Sheikh Aftabuddin; Mohammad Zafar; Md. Abdul Kader (Advances in Aquaculture and Fisheries Management, 2020)
A study was conducted between January - August, 2006 concerning the Penaeus monodon fry marketing systems in Bangladesh based on the existing one and economic evaluation of marketing activities. In Bangladesh, P. monodon fry marketing of the wild and hatchery reared ones is almost exclusively handled by private entrepreneurs. The Government of Bangladesh has no command on this issue except the banning of wild fry catching. The market chain from fry catchers or fry producers to shrimp farmers passes through a number of intermediaries: fry faria, fry traders, fry commission agents and retailers. The existing marketing system is buyer-driven chains where producers that is shrimp hatchery owners have little ability to influence the price, on the other hand, wild fry catchers or small farias dependent on the dominant buyers or larger arathdars. The fry value chain is complex, different intermediaries of each node of the chain is an important actor to determine the fry value. The price differences between hatchery fry producer and the shrimp farmers was 250 BDT while wild fry catcher and shrimp farmers was 450 BDT. The farias, arathdars, traders and commission agents purchase P. monodon fry from the fry catchers, hatcheries and from one another and they trade in different volumes across different regions. Moreover, these agents usually run on a commission basis and charged 50 BDT per 1000 fry selling while the price was higher than 250 BDT per 1000 fry and charged 20 BDT while the fry price is lower that is, below 250 BDT per 1000 fry.